(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2022)
Amid these pandemic times, we hope that everyone is well and healthy. This editorial is dedicated to those fighting scientific denialism and social oppression. Thus, it is with joy that we write this text to the readers of RBPEC, to begin a dialogue about our journal. The Brazilian Journal of Research in Science Education was established in 2001 and officially launched at the III National Meeting of Research in Science Education (III ENPEC), which was held in Atibaia, SP, between November 7th-10th, 2001. The journal has been published three times annually since then and adopted a continuous publication mode in 2019. As you may know, the journal has been not only classified as A2 according to QUALIS CAPES (the Brazilian official system for classifying scientific production) between 2013-2016 in the fields of Education and Teaching, but also indexed in databases such as DOAJ, Latindex, IRESIE, Redalyc, among others. This demonstrates its role in terms of dissemination within our field of knowledge, which is the result of a collective work between editors, peers, and authors. We are thankful to all of you who make part of RBPEC, for your collaborative, solidary and voluntary work.